If you're seeing this message, it means we're having trouble loading external resources on our website.

If you're behind a web filter, please make sure that the domains *.kastatic.org and *.kasandbox.org are unblocked.

## Algebra 1

### Course: Algebra 1>Unit 5

Lesson 1: Intro to slope-intercept form

# Intro to slope-intercept form

Slope-intercept form (y=mx+b) of linear equations highlights the slope (m) and the y-intercept (b) of a line. Watch this video to learn more about it and see some examples.

## Want to join the conversation?

• My teacher actually said something about "rise over run." Could you talk little bit more about it?
• rise/run is basically another term name for y/x because for the "y" axis it rises or goes up vertically and the "x" axis runs or goes across horizontaly.
• What is the difference between y=mx+c and y=mx+b?
• Nothing... They just use different variables for the y-intercept.
• I'm confused, by how did he got (y - 5) = 2 (x - 1) also can somebody reply quick because I'm just stuck right now
• I dont like this unit
• i agree
• How many different way can you write an equation?
• Infinitely many. You can rewrite equations by performing algebraic manipulations, making sure you always do the same operation on both sides of the "=" sign. So you could add 1 to both sides, and now it's written a new way. Or add 2 to both sides, or add 9, or subtract 3.5, or multiply by 617.8, etc.
• i think my brain is broken i don't understand any of this
• same
• Sometimes, I see slope intercept form written as "y=mx+a" instead of the typical y=mx+b. There are other variations of it like y=m(x-a). Could anyone articulate on this variation of slope intercept form?
• The forms y=mx+b and y=mx+a are essentially the same, except for the naming of the constant term. The form y=mx+b means slope m and y-intercept b; similarly, the form y=mx+a means slope m and y-intercept a.

The form y=m(x-a) is essentially different from the other two forms, and means slope m and x-intercept (instead of y-intercept) a.

Have a blessed, wonderful day!
• I read that y=m(x-a) is slope-intercept from, where m=slope and a=x-intercept. How do you derive that from the simpler slope-intercept form?
• As noted in your other post, rather than being derived from the slope intercept form, it is a variation of the point slope form, y - y1 = m(x-x1) where the point is (x1,y1) and the slope is m. Since the x intercept is where y = 0, the point would revert to (x1,0), thus reaching your form of y=m(x-x1), merely substituting a for x1 does not change the formula.